Plan estratégico de mejoramiento de la finca ganadera La Palancana, de la parroquia Cariamanga, cantón Calvas, provincia de Loja - Soto Montero, Alex Jefferson (2015)
This research paper called "STRATEGIC FARM LIVESTOCK IMPROVEMENT PLAN THE PALANCANA, CARIAMANGA PARISH, CANTON BALD LOJA PROVINCE", aimed to: Make a diagnosis of the farm which will reveal its weaknesses and Fortaleza's.- Define improvement strategies. Propose an improvement plan for the property; and share the results. The methodology used was the realization of FODA analysis, then the strategies were raised and finally the projects were defined. The items contained in the plan are: Diagnostic Company: Strengths and weaknesses, opportunities and threats. Defining the Vision, Mission, Objectives and Policies of the Company. Selection Strategies. Selection of projects and activities. General and operational planning of the Strategic Plan The results achieved are: The La Palancana has a total area of 12.5 hectares, of which 10.5 hectares are planted with grass for grazing and 2 permanent pasture has cut as maralfalfa, kingras, Cariamanga and sugarcane. The varieties of grasses of the paddocks are: Chile, Kikuyu, brachiaria and some weeds. Existing livestock breeds on the farm are: Holstein, Brown Swiss and Brown Swiss Holtein by. The average milk production is 10 liters / cow day; Likewise, there are buildings for livestock management as a stable, corral, cement drinkers, wine cellar and a room for cowboy. The main problems of the farm are: The farm operates in a planned way, nor has formulated a work plan. Monitoring and control of the activities of the farm is minimal. An accounting system is not carried on the farm. We need to build a reservoir to capture groundwater. Pasture irrigation is done with water from a creek that leads sewage. No soil aeration by plowing. Zero equalization or grassland renewal thereof. Dispersion of feces is never performed. Low pastures subscriber. . The milk is sold raw is not industrialized. This small number of animals (16 cows), the estate .The irrigation by gravity, causing erosion risk; and the employee has not been trained in the technical management of livestock. Strengths of the property are: The owner of the farm has farm management skills; it is also a veterinary professional thus ensuring technical management of cattle herd. It has good borrowing capacity. There are buildings such as barn and corral in good condition for handling animals. Good livestock genetics. Reproduction is by artificial insemination. The main projects and activities defined for the farm are: Implementation of the development plan for the La Palancana, 2016-2020. Design of software for the control de la farm management. Construction of a dump to collect the feces of animals. Hiring an accountant to take occasional accounting of the estate. Purchase vaconas to increase the dairy herd. Construction of a local roof to keep the cows at night. Construction of a water reservoir on the farm. Soil fertilization. Construction of a sprinkler system. Industrialization of milk; and Promotion of the resources available to the farm.